A bibliometric analysis of the top cited articles on anterior cruciate ligament reconstruction with anterolateral ligament reconstruction - Osama Z., Alzobi (2024)
BackgroundIn recent years, there has been a marked increase in research interest in anterior cruciate ligament (ACL) reconstruction combined with anterolateral ligament (ALL) augmentation. PurposeThis study aims to provide a thorough bibliometric analysis of the most influential articles focused on ACL reconstruction with ALL augmentation. Study designCross-sectional study. Level IV. MethodsIn July 2024, a systematic search was conducted using the Web of Science Core Collection and Google Scholar databases to identify relevant publications on ACL reconstruction with ALL augmentation. The top 50 cited articles that met specific inclusion criteria were carefully documented and analyzed in a comprehensive bibliometric review. ResultsThe top 50 cited articles were published between 2013 and 2020. Citation counts per article ranged from 87 to 1000, with an average citation count of 207.18 and a citation density ranging from 12.43 to 90.91. The United States emerged as the leader in both the number of publications and total citations, followed by France and Brazil. Most of the articles were focused on anatomical and biomechanical studies, with a notable lack of high-evidence-level studies; only 2 articles were classified as level 2 evidence, and none as level 1. ConclusionAll of the top 50 most cited articles were published between 2013 and 2020, highlighting their recent significance in the scientific community. The diversity of study types, predominantly anatomical and biomechanical, reflects widespread interest in the subject, though there is a noticeable gap in high-evidence-level research. The United States and France are the primary contributors to this body of work. This review offers important insights into global research trends and suggests potential directions for future studies.